Alternative seafood: Assessing food, nutrition and livelihood futures of plant-based and cell-based seafood - Marwaha, Nisha; Beveridge, Malcolm C. M.; Phillips, Michael J.; Komugisha, Basiita Rose; Boso, Delvene; Chan, Chin Yee; Kabir, Kazi Ahmed; Sulser, Timothy B.; Wiebe, Keith D. (WorldFish, 2020)
This report sets out to explain and explore the emerging alternative seafood sector. It focuses on identifying research questions regarding the implications of alternative seafood for food and nutrition security, livelihoods and the environment in low- and middle-income nations. The report presents an overview of both the “conventional seafood” sector, comprised of fisheries and aquaculture, as well as the alternative seafood sector. A sustainable food systems framework has been adopted to elaborate the implications, opportunities and challenges of the alternative seafood sector for food and nutrition security, livelihoods and the environment, now and over the next decade. The research involved a review of literature and mass media as well as interactions with diverse stakeholder groups, including development specialists and stakeholder groups involved in production, investment, research, retail and advocacy of conventional and alternative seafood. Together with the International Food Policy Research Institute (IFPRI), we developed preliminary future growth scenarios for the plant- and cell-based seafood subsectors over the next decade. These were used to explore how their projected growth might impact global seafood supply and demand and to examine the utility of the International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) in informing decision-making and prioritizing research.